The Leeds Symposium on Food History and Traditions: Its Origin and Progress - Wilson, C Anne (Petits Propos Culinaires, 2014)
A memoir and history of the history of the Leeds Symposium on Food History and Traditions, its connection to the book collector, Mr John F. Preston, to the Brotherton Library at the University of Leeds. The author recounts her own trajectory within the world of food history and various contacts she made in the course of her research, all of whom were instrumental in founding the Symposium which was launched in 1986.